1)x-(x+y) - (x-y)

2)-0,16+(4,06-m)=

3) 5a+b-5b+a

4) 5a+7a-9,2m+15m

5) -9x+7x+5y+7x

6) 30x-30+12+15x

7) 2 умножить (7x-3) +3 умножить (4х-2)

8) 2 умножить (3х-11)-5 умножить (4-3х)

9) 6m- (4m-3) + (3m-4)

10) - 3 умножить (c+4) - (3c-5) при c=2,5

11) 3,3- (x-6,7)=100 (уравнение)

12) 2 умножить (3x+8) - (5x-7)=0 (уравнение)

1

Ответы и объяснения

2013-01-18T19:06:56+04:00

1)x-(x+y) - (x-y) =x-x-y - x+y=- x

2)-0,16+(4,06-m)=-0,16+4,06-m=3,9-m

3) 5a+b-5b+a=6a-4b

4) 5a+7a-9,2m+15m=(5a+7a)-(9,2m+15m)=12a-24.2m.

5) -9x+7x+5y+7x=5х+5у=5(х+у)

6) 30x-30+12+15x=15х-18=3(5х-6)

7) 2 умножить (7x-3) +3 умножить (4х-2)=14х-6+12х-6=2х

8) 2 умножить (3х-11)-5 умножить (4-3х)=6х-22-20+15х=21х-42=21(х-2)

9) 6m- (4m-3) + (3m-4)=6m- 4m+3+ 3m-4=5m-1

10) - 3 умножить (c+4) - (3c-5) при c=2,5=-3c-12-3c+5=-6c-7

при с =2,5= -6*2,5-7=-15-7=-22

 

11) 3,3- (x-6,7)=100 (уравнение)

   3,3- x+6,7=100

   10-х=100

    х=-90

Ответ:-90

12) 2 умножить (3x+8) - (5x-7)=0 (уравнение)

       6х+16-5х+7=0

      х+23=0

       х=-23

Ответ:-23